Effect of pectin and citric acid on sensory evaluation for consumer’s acceptability of preserved guava jelly - Chaudhry, Gul-e-Saba (Research Journal of Pharmacy and Technology, 2024)
This study investigated the interaction of different pectin and citric acid concentrations on sensory evaluation for consumers' acceptability of economically preserved guava jelly. Fresh Psidium guajava (guava) jelly prepared with 0.15%, 0.2%, and 0.25% pectin and with 1.1%, 1.15%, and 1.2% citric acid as preservative. There are no additional preservatives added during the processing of jelly. A taste panel consisting of fifteen panelists adjudged the samples' acceptability for sensory evaluation. The test method (Nine points Hedonic rating) was used for the color, Texture, flavor, and overall acceptability of guava jelly, which was analyzed via One-way ANOVA statistical analysis. The jelly's pectin and citric acid composition regulated the color, flavor, and texture scores. Mean sensory scores of color ranged from 5.07−5.40, 5.33−7.80, and 5.60−7.33 for jellies with 0.15%, 0.20%, and 0.25% and 5.17−5.53, 5.58−5.80 and 6.07−6.83 for jellies in 1.1%, 1.15% and 1.20% pectin and citric acid respectively. Moreover, the highest color was observed for 0.25% and 1.20% pectin and citric acid treatment. However, the mean flavor score was the highest for sample P3 (0.25% pectin) and sample C3 (1.20% citric acid). Finally, the overall best acceptability of the sample was noticed till 90 days, with 0.25% pectin and 1.2% citric acid formulation. © RJPT All right reserved.